Perancangan Media Informasi Sentra Wisata Kuliner Wonorejo di Kota Surabaya Berbasis Website Menggunakan Metode Model View Controller - Iqbal Ramadhani Mukhlis (Diponegoro University, 2023)
Surabaya possesses considerable potential for economic growth and the tourism industry. The Surabaya City Government is actively harnessing this potential, one of which involves establishing the Culinary Tourism Center to introduce a variety of traditional Surabaya cuisine. Specifically, the Surabaya City Government has initiated the creation of the Wonorejo Culinary Tourism Center (SWK) to showcase the iconic Surabaya dishes. In pursuit of this objective, an information platform, based on a website, has been developed using PHP programming technology and a MySQL database, employing the Model View Controller approach supported by the CodeIgniter framework. This website is intended to furnish information about the diverse Surabaya dishes accessible at the Wonorejo Culinary Tourism Center to the local community and visitors from beyond Surabaya. The research process encompasses various methodologies, including literature review, observation, interviews, and surveys. The research findings, which encompass both internal and external testing, indicate a success rate of 80.67%. These results signify that this information platform is a valuable tool for facilitating the acquisition of information about the legendary and other culinary offerings available at SWK Wonorejo, benefiting visitors from Surabaya and beyond.